The effect of Nb on the formation of TiO2 anodic coating oxide on Ti–Nb alloys through MAO treatment - Kuroda, Pedro Akira Bazaglia [UNESP] (2024)
This study aims to promote the growth of a porous oxidized coating of TiO2 due to oxidation of the surface of the Ti–Nb alloy substrates (Nb = 5, 10, and 25 wt%) using the micro-arc oxidation (MAO) technique. Using structural (x-ray diffraction) and microstructural (optical, confocal, and scanning electron microscopy) characterization techniques, it was observed that Nb promotes the formation of the β phase in Ti alloys, reducing Vickers microhardness and elastic modulus values. Regarding the MAO coating, the results showed that the TiO2 coatings are in the form of anatase and rutile, where Nb promotes the formation of the rutile phase, increasing the hardness of the coatings. MAO coatings have high roughness values due to the formation of porous structures characteristic of MAO surfaces. Adhesion results show that MAO coatings have low adhesion with the substrate.